Active Wnt proteins are secreted on exosomes - Groß, Julia Christina; Chaudhary, Varun; Bartscherer, Kerstin; Boutros, Michael (Nature cell biology, 2012)
Wnt signalling has important roles during development and in many diseases. As morphogens, hydrophobic Wnt proteins exert their function over a distance to induce patterning and cell differentiation decisions. Recent studies have identified several factors that are required for the secretion of Wnt proteins; however, how Wnts travel in the extracellular space remains a largely unresolved question. Here we show that Wnts are secreted on exosomes both during Drosophila development and in human cells. We demonstrate that exosomes carry Wnts on their surface to induce Wnt signalling activity in target cells. Together with the cargo receptor Evi/WIs, Wnts are transported through endosomal compartments onto exosomes, a process that requires the R-SNARE Ykt6. Our study demonstrates an evolutionarily conserved functional role of extracellular vesicular transport of Wnt proteins.
Published online 16 September 2012
Gesehen am 07.06.2018